There was an old lady who swallowed a bat! - Colandro, Lucille; Lee, Jared D. (New York Scholastic, 2002)
In this variation on the traditional cumulative rhyme, a woman swallows a bat, an owl, a cat, a ghost, and other things and creatures associated with Halloween.
"Cartwheel books."
Keywords: Folk songs, English -- Texts; Folk songs; Nonsense verses